CARBONIC ANHYDRASE, GROWTH, AND MOLTING OF MUD CRABS (Scylla sp.) GIVEN SPINACH (Amaranthus sp.) EXTRACT - Sutrisno, Bagas Gagat Rahina Asihing; Hertika, Asus Maizar Suryanto; Supriatna, Supriatna (Journal of Environmental Engineering and Sustainable Technology, 2025)
This study aimed to evaluate the effect of spinach (Amaranthus hybridus) extract containing phytoecdysteroids on molting duration, growth performance, feed efficiency, and carbonic anhydrase (CA) enzyme activity in mud crabs (Scylla sp.) reared in a Crab Apartment Box (CAB) system. A Completely Randomized Design (CRD) was applied with four levels of spinach extract doses (0, 300, 700, and 1000 ng/g body weight) and three replications. The results showed that the administration of spinach extract significantly shortened molting duration, with the highest dose (1000 ng/g) reducing the average molting period to 11.83 days compared to 39.17 days in the control group. Although absolute weight gain decreased at higher doses, specific growth rate (SGR) and feed efficiency improved, and feed conversion ratio (FCR) declined. While weight gain percentage slightly decreased at higher doses, overall metabolic efficiency improved. Enzymatic analysis revealed that CA activity peaked at 300 ng/g, suggesting optimal ionic regulation during post-molt recovery at this dose. However, higher doses caused a decline in CA levels, potentially due to regulatory feedback or physiological stress. These findings demonstrate the potential of spinach extract as a natural molting accelerator and physiological modulator in soft-shell crab production.